An Innovative Approach to the Development of Communicative Competence in Students - Shavkatovna, Shavkatova Dilbar (European Journal of Life Safety and Stability (2660-9630), 2022)
Communicative competence is defined as the ability to interact effectively with others. At its most basic, competence is seen as a combination of language aptitudes an individual has for learning a foreign language. Such potential contributes to his/her attaining high levels of performance. This paper considers the following: the nature of communicative competence and some of its models; the importance of developing communicative competence among students; and the implications of communicative competence in English language teaching and learning.